2006
DOI: 10.1159/000091642
|View full text |Cite
|
Sign up to set email alerts
|

Potential Clinical Correlates and Risk Factors for Interatrial Block

Abstract: Background: Interatrial block (IAB; P wave ≧110 ms) denotes a conduction delay between the atria, is strongly associated with atrial tachyarrhythmias, left atrial enlargement, left atrial electromechanical dysfunction, and is a risk for embolism. Despite this, potential risk factors for IAB have not been clearly defined. Methods: Patients admitted via the Emergency Department for nonacute medical reasons to the nontelemetry general medical floors of a tertiary care general hospital from October to November 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…We had previously demonstrated that coronary artery disease and its perennial risk factors such as hypertension, diabetes mellitus and hypercholesterolemia could be potential risk factors for developing of interatrial block [12]. These comorbidities presumably exert their deleterious effects by encumbering the Bachmann Bundle (the principal interatrial pathway) either directly, by altering atrial properties or indirectly, via ischemia of its vascular supply (sinoatrial nodal artery and its branches).…”
Section: Potential Underlying Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…We had previously demonstrated that coronary artery disease and its perennial risk factors such as hypertension, diabetes mellitus and hypercholesterolemia could be potential risk factors for developing of interatrial block [12]. These comorbidities presumably exert their deleterious effects by encumbering the Bachmann Bundle (the principal interatrial pathway) either directly, by altering atrial properties or indirectly, via ischemia of its vascular supply (sinoatrial nodal artery and its branches).…”
Section: Potential Underlying Mechanismsmentioning
confidence: 99%
“…Atrial fibrillation (16) No atrial fibrillation (69) that prolongation of interatrial conduction is thought to be the main operative mechanism in atrial fibrillation, either risk factor, if not both, could have a multifarious relationship with interatrial block or its sequelae [12,13]. Indeed, hypertension, be it alone or in concert with interatrial block, could also trigger remodeling of the left atrial and potentiate its subsequent dysfunction, further contributing to the vicious cycle that increases the risk of atrial fibrillation [2,3,12].…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Established cardiovascular risk factors such as hypertension, hyperlipidemia and diabetes mellitus are frequently prevalent in patients with partial and advanced IAB [2, 11]. It is not surprising therefore that myocardial ischemia has been implicated as a potential cause for worsening interatrial conduction [12].…”
Section: Discussionmentioning
confidence: 99%
“…The principal pathophysiology is quite likely centered around an ischemic focus pertaining the Bachmann Bundle, where impairment of its vascular supply (thought to be mainly the sinoatrial nodal artery and its branches) could be a leading cause. Indeed, we had previously delineated the potential association of interatrial block with underlying coronary artery disease, hypertension, diabetes mellitus and hypercholesterolemia, all potent harbingers of atherosclerosis [4]. More importantly, increase in P-wave durations has also been shown to occur with cardiac ischemia [5][6][7], particularly in patients with coronary artery disease who undergo exercise tolerance [5,8].…”
Section: Introductionmentioning
confidence: 99%